Coal marketing in South Africa: the intricasies of product, distribution, price and promotion in domestic and export markets - Steyn, Melanie (My University, 2010)
The study aims at examining all the individual activities during the marketing process of bulk commodity coal. This involves integrating all the concepts of the marketing mix, namely: product, price, distribution and promotion. The marketing mix elements all focus on industrial marketing fundamentals, which are essentially different to those in usual product and service marketing. The marketing mix is discussed in theoretical and practical detail which is essential for reaching markets at optimal pricing structures to ensure the longevity of the producing company. The research was conducted on an exploratory descriptive basis. The study focuses on ESKOM, Domestic Sales and Export Sales ex Richards Bay Coal Terminal, as the three existing markets for coal in South Africa. Reference is made to Durban and Maputo Terminals as alternative ports for coal exports from South Africa.